2021
DOI: 10.1093/humupd/dmab002
|View full text |Cite
|
Sign up to set email alerts
|

Immediate versus postponed frozen embryo transfer after IVF/ICSI: a systematic review and meta-analysis

Abstract: BACKGROUND In Europe, the number of frozen embryo transfer (FET) cycles is steadily increasing, now accounting for more than 190 000 cycles per year. It is standard clinical practice to postpone FET for at least one menstrual cycle following a failed fresh transfer or after a freeze-all cycle. The purpose of this practice is to minimise the possible residual negative effect of ovarian stimulation on the resumption of a normal ovulatory cycle and receptivity of the endometrium. Although electi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The success of ET relies on synchronization between the embryo and endometrium so that the endometrium is optimally receptive for the embryo to implant [9,22]. Previous studies had investigated that women with repeated implantation failure (RIF), personalized timing for transfer resulted in a higher clinical pregnancy rate compared with routine protocol [23][24][25]. Thus, although there is a bene t favoring blastocyst transfer in fresh cycle, it remains unclear whether the day of transfer impacts on pregnancy rate [4].…”
Section: Discussionmentioning
confidence: 99%
“…The success of ET relies on synchronization between the embryo and endometrium so that the endometrium is optimally receptive for the embryo to implant [9,22]. Previous studies had investigated that women with repeated implantation failure (RIF), personalized timing for transfer resulted in a higher clinical pregnancy rate compared with routine protocol [23][24][25]. Thus, although there is a bene t favoring blastocyst transfer in fresh cycle, it remains unclear whether the day of transfer impacts on pregnancy rate [4].…”
Section: Discussionmentioning
confidence: 99%
“…The reviews are based on retrospective data including a variety of FET protocols, hence, the presence of selection bias is apparent and the quality of evidence is low. Despite a significant overlap in studies included in the reviews, the results differ slightly, probably due to inclusion of unadjusted 14 versus adjusted 15 results. Huang et al reported no significant association between timing of FET and pregnancy outcomes; clinical pregnancy rate (CPR) (relative risk (RR) 0.94 (95% CI 0.87 to 1.03)) and live birth rate (LBR) (RR 0.94 (95% CI 0.85 to 1.03)) while Bergenheim et al found a slightly higher CPR (adjusted OR (aOR) 1.22 (95% CI 1.07 to 1.39)) and LBR (aOR 1.20 (95% CI 1.01 to 1.44)) in immediate versus postponed FET.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, more and more young cancer patients accept fertility preservation services at present since they receive certain types of cancer surgery which lead to removal of organs needed for a pregnancy, and certain therapy might increase hormone levels or cause damage to a female’s eggs ( 7 ). Previous studies have not come to a definitive conclusion on how immediate or delayed resuscitation will benefit pregnancy rates ( 8 , 9 ). Additionally, many of the retrospective studies on this issue were conducted in years ago, and the results of these studies may be biased against changes in the existing COH protocols ( 1 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%